MODEL MATEMATIK UNTUK MEMPREDIKSI KEKASARAN PERMUKAAN HASIL PROSES CNC BUBUT PADA KONDISI PERMESINAN TANPA PENDINGIN - Saputro, Herman (PAWIYATAN, 2013)
Turning is one of the machining operations that widely used in variety of manufacturing industries. The quality of surface plays very important role in the performance of turning that significantly improves fatigue strength, and corrosion resistance. It is also affects functional attributes of parts such as light reflection, coating and heat treatment. This research aim to develop a mathematical model to predict surface roughness based on machining parameter selected (spindle speed, feed, and depth of cut) with cutting codition dry. The experiment was tested by using Trun Master TMC 320 Sinumerik 802 S machining center. After 27 specimens were cut for experimental purposes, they were measured off-line with a surface roughness tester to obtain the roughness average value. The surface roughness (Ra) could be predicted effectively by applying spindle speed (n), feed rate (Vf) and depth of cut (a) in the multiple regression model as: Y = -0.1228 Ã¢â¬â 0.0001 n + 20.940 Vf + 0.7444 a. TheÃÂ average percentage deviation of the testing set was 6.429 %ÃÂ for training data set This showed that the statistical model could predict the surface roughness with about 93.571 % accuracy of the testing data set.ÃÂ Keywords : CNC Turning, Surface Roughness, Multiple Linier RegressionÃÂ